How I Do It: Transperineal prostate biopsy using local anesthetic in an outpatient setting - Ordones, Flavio Vasconcelos [UNESP] (2023)
Transperineal prostate biopsy (TPPB) is proven to be an effective diagnostic tool for prostate cancer detection. It allows satisfactory sampling of apical and anterior areas which is not well achieved with the transrectal route, without the associated risks of urinary tract infection or sepsis. The main objective of this paper is to describe the technique utilized in our institution to perform transperineal prostate biopsy under local anesthetic in the outpatient clinic setting.